Modelling of distribution and geometry of lithological complexes of the Ecca Group (the Karoo Supergroup) in SW Botswana - Wendorff, Marek; Radwański, Lechosław; Papiernik, Bartosz (Geology, Geophysics and Environment, 2013)
The Ecca Group, a subdivision of the Karoo Supergroup (U. Carboniferous-L. Jurassic) in SW Botswana is a sequence deposited as marine deltaic bodies considered to have been supplied from a cratonic source elevated north of the basin. The Karoo strata in this region are covered unconformably by sands of the Kalahari Beds (Upper Cretaceous – Recent). Therefore the bedrock outcrops are extremely rare, limited in size and a low number of boreholes drilled in this vas area (ca. 340 x 540 km) provide the only insights into the succession of the Karoo Supergroup. Very long distances between individual boreholes make correlation, interpolation between localities and interpretations of geometry of lithological bodies that would provide clues supporting basin analysis by traditional means very problematic. Therefore, modelling of the Ecca Group lithofacies associations with the use of Petrel software was performed, which resulted in the first approximation of the space-time relations between lithological complexes of this unit. These relations in turn suggest evolutionary trends of the basin during deposition of the Ecca Group strata.The model suggests two main zones of supply indicated by two distinctly different patterns of deltaic lithofacies associations, and their evolution controlled by post-Dwyka palaeotopography and its subsequent modifications by local subsidence in the centre of the depository. Initially rapid southward progradation of relatively fine-grained delta body located in the west of the area was followed by subsidence-induced aggradation interrupted by stages of abandonment and marine transgression. Such variations, emphasised by the presence of sandy clinoforms of the delta lobes separated by basinal ‘fines’, imply significant interplay between rates of supply and subsidence. On the other hand, the delta formed in the east contains relatively high proportion of coarse-grained sandstone facies overlying prodelta fines as laterally extensive tabular body formed most probably by lateral migration of distributary channels and delta-front mouthbars, and devoid of abandonment stages. Proximal litofacies of the “western delta” fill the subsiding depocentre and grade distally into synchronously deposited prodelta fines towards the south. By contrast, distal fine-grained prodelta facies fill basin depocentre in the eastern area and are overlain by proximal facies of the “eastern delta”.